Karakteristik Sensoris Fillet Ikan Patin (Pangasius sp.) dengan Penambahan Ekstrak Purun Tikus (Eleocharis dulcis) - Ace Baehaki; Herpandi Herpandi; Rosalina Rosalina (Universitas Sriwijaya, 2019)
This study aims to determine the effect used of Eleocharis dulcis extract on fish fillet catfish (Pangasius sp.) which stored cold temperatures. Several stages were carried out including sampling, sample preparation, sample extraction, and making fish fillet catfish (Pangasius sp.). Extraction with multilevel maceration with a sequence of solvents n-hexane, ethyl acetate, and ethanol. The parameters observed were hedonic test in the form of appearance, aroma, and texture. This research was conducted nonparametric data analysis using two sample related test methods. The results showed that there were significant differences in the values of appearance, aroma, and texture.